The quality of life of patients with ovarian cancer stage I-III via general questionnaire EQ-5D and the special questionnaire EORTC QLQ-C30 - V. N. Zhurman; E. V. Eliseeva; A. P. Gulevich; M. V. Volkov (Izdatelstvo OKI, 2018)
In order to assess the impact of treatment on quality of life of patients with ovarian cancer stage I-III, we have conducted monitoring of 51 patients who were treated in The Primorsky Krai Oncological Clinic from 2014 to 2015, who responded to the overall EQ-5D questionnaire and the special questionnaire EORTC QLQ-C30 before treatment and after 6 cycles of chemotherapy. All patients were subjected to the surgery at the first stage. Laparotomia, hysterectomy with appendages, resection of the greater omentum is made for 41 (80,4%) patients, without resection of the omentum was made for 3 (5,9%) patients. Laparotomia, uppervaginal amputation of uterus with appendages, resection of the greater omentum is made 5 (9,8%), without resection of the omenntum was made for 2 (3,9%) patients. The omentum was not removed owing to a lack of technical capacity for resection. The second stage of the complex treatment is adjuvant chemotherapy scheme TCb (Paclitaxel 175 mg/m2 Carboplatin AUC 6) or Paclitaxel 175 mg/m2, Cisplatin 75 mg/m2 (total 6 cycles). Pronounced changes in the quality of life of patients before treatment was owing to the manifestation of the underlying disease, the lack of «expressed concerns» after treatment indicates the effectiveness of anticancer therapy. The increase of «moderate problem» by the components «daily activity», «anxiety and depression», «health condition», compared with how it was a year ago,» indicates the presence of side effects of chemotherapy. The quality of life assessment via special questionnaire EORTC QLQ-C30 before treatment and after chemotherapy in patients with stage I ovarian cancer shows significant changes in indicators in the growth of dyspeptic symptoms, improvement of the emotional background (decrease anxiety and depression, sleep), reduced performance of significant physical activity. At the stage II ovarian cancer after chemotherapy increase in a general weakness, a limitation in the performance of daily activities and significant physical exertion are marked. At the stage III ovarian cancer substantial significant changes are noticed as the growth of dyspeptic symptoms, emotional depression, but also at the performance of daily activities and physical exercise, in spite of this, patients assessed the overall health status over the last week by 6 points, where 7 points is excellent health condition. Results show the decrease of the quality of life, in the background of the special treatment and the stage of disease.